Developing and Validating Gamified English Teaching Materials to Enhance Achievement in Indonesian Elementary Schools - Muhammad Asrul Sultan; Baso jabu; Nurhikmah H (Cita konsultindo, 2025)
This study systematically investigates the design, validation, and effectiveness of gamified English teaching materials tailored for Grade 5 learners in Parepare, Indonesia, within the framework of a Research and Development (R&D) based on the Alessi & Trollip model, materials were developed in three phases: Planning (needs analysis), Design (module drafting), and Development (validation and pilot implementation). Sixty students across two schools participated in pre- and post-tests, expert validation (N=3), practicality surveys (teachers N=4; students N=60), classroom observations, and interviews. Experts rated content validity at 92%; practicality exceeded 85%; and paired-sample t-tests showed significant improvement from pre-test (M=61.35, SD=7.12) to post-test (M=80.21, SD=6.45), p<.001. These results confirm that integrating game elements such as points, badges, levels, and narrative quests can substantially enhance engagement and EFL achievement among young learners.